ANALISA PANGGILAN TUHAN DALAM KONTEKS MASYARAKAT MAJEMUK DI TINGKAT SEKOLAH - Hasahatan Hutahaean; Robert Patannang Borrong; Stenly Reinal Paparang; Riste Tioma Silaen; Asmat Purba (Phronesis: Jurnal Teologi dan Misi, 2023)
This study aims to find a conception for Christian students of how to understand God's call for Christian students, especially in roles in a pluralistic society. As a large nation consisting of various elements, Christian students in Indonesia cannot stand still and surrender. At the same time, it is asked to answer God's call by portraying oneself elegantly in plurality. Research is conducted with qualitative methods to find clear and correct understanding and guidance. Data was obtained from selected literature based on the suitability of variables and needed part of the answer to the research problem. The result is that differences in ethnicity, culture, religion, and social level are loopholes to carry out God's call in a pluralistic society. Practising a calm attitude and acting out religious moderation is the right way for students to attend school. Research emphasizes that student fellowship in schools is a measured and guided effort to maintain students' faith and trust. Through the fellowship, Christian values and education can be instilled. God's call becomes light, and salt in society can be realized. The diversity of society is precisely God's way for Christian students to answer the divine call.